Hydrological changes in the Upper Yellow River under the impact of upstream cascade reservoirs over the past 70 years - Jing Hu; Xiong Zhou; Yujun Yi; Chunhui Li; Xuan Wang; Qiang Liu; Jiansu Mao (Journal of Hydrology: Regional Studies)
Study region: The Upper Yellow River Basin (UYRB), China. Study focus: In this study, a variety of mathematical statistical methods, the Indicators of Hydrologic Alteration—Range of Variability (IHA-RVA) method, and the newly proposed Flow Surplus-Deficit (QS-QD) method were integrated to analyze the impact of cascade dam development on hydrological changes over the past 70 years in the UYRB. Additionally, the Double Mass Curve (DMC) method was utilized to evaluate changes in annual sediment transport, quantifying the influences of precipitation and human activities. New hydrological insights for the region: Long-term statistical analysis revealed significant declining trends in both the annual runoff and sediment load following dam construction. Abrupt changes in runoff and sediment were identified during the study period in 1969 and 1987. Dam operations have altered the relationship between water and sediment, resulting in intensified summer flow deficits and winter-spring flow surpluses, with significant increases in flow deficit during July. The operation of the Longyangxia Reservoir and Liujiaxia Reservoir cascade systems exhibits cumulative effects over time and space. The proposed QS-QD method quantitatively estimates monthly flow variations and effectively addresses the limitations of RVA variation based on frequency. Furthermore, sediment transport at hydrological stations indicated a sequential downstream decrease, with human activities contributing between 95.93 % and 116.51 % to these changes.